PENGEMBANGAN INSTRUMEN TES BERBASIS HIGHER ORDER THINKING SKILL (HOTS) MATERI KESETIMBANGAN KIMIA DI KELAS XI SMA/MA - Nesta Netri; Betty Holiwarni; Abdullah Abdullah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The research developmnet of test instruments based higher order thinking skill is aimed to develop a valid and reliable test instruments on chemical equilibrium subject. This research method is research development (Research and Development, R & D) with 4-D development model with includes stages define phase, Design, Develop and Disseminate. Instruments of data collection are used validation and test sheet. Data analysis technique is by calculating the percentage score of validation and reliability with alpha cronbach’s formula. Instrument test consists of 8 items essay. The result showed that instruments test based higher order thinking skill developed valid criteria of materials, construction, and languange aspect with a percentage i a row 97,5%, 91,16%, and 96,25%. The test insrumets is also considered reliable with alpha cronbach value of 0,71 in high category.Key Words: Test Instruments, Higher order Thinking Skill, Chemical Equilibrium